Efeitos da calagem na fertilidade do solo e na nutrição e produtividade da goiabeira - Natale, William [UNESP]; Prado, Renato de Mello [UNESP]; Rozane, Danilo Eduardo [UNESP]; Romualdo, Liliane Maria [UNESP] (Sociedade Brasileira de Ciência do Solo, 2007)
A acidez do solo é um dos mais importantes fatores que limitam a produção em regiões tropicais. Assim, o objetivo deste trabalho foi avaliar os efeitos da calagem na fertilidade do solo e na nutrição e produtividade da goiabeira (Psidium guajava L.). O experimento foi realizado na Estação Experimental de Citricultura de Bebedouro, São Paulo, em um Latossolo Vermelho distrófico (V = 26 % na camada de 0-20 cm), no período de agosto/1999 a julho/2006. As doses de calcário empregadas foram: 0; 1,85; 3,71; 5,56 e 7,41 t ha-1. Durante 78 meses após aplicação do corretivo foram realizadas análises químicas de solo. Foi feita avaliação do estado nutricional e da produtividade durante cinco safras agrícolas. A calagem promoveu alteração nos atributos químicos do solo ligados à acidez, elevando o pH, Ca, Mg, soma de bases (SB) e saturação por bases (V) e diminuindo H + Al, até 60 cm. Os teores foliares de Ca e Mg aumentaram com as doses de calcário. As maiores produções acumuladas de frutos estiveram associadas a um valor de V de 50 % na linha e 65 % na entrelinha das goiabeiras.

Soil acidity is one of the most important constraints to agricultural production in the tropics. For this reason, the objective of this research was to evaluate the effects of soil liming on the performance of guava (Psidium guajava L.) trees. The experiment took place at the Citrus Experimental Station in Bebedouro, state of São Paulo, Brazil. The soil was a Typic Haplustox (V = 26 % in the 0 to 20 cm layer) between August 1999 and July 2006. The following doses of limestone were employed: 0, 1.85, 3.71, 5.56, and 7.41 t ha-1. During the 78 months after starting the experiment, soil chemical attributes were periodically examined. Over a period of five years, the guava tree leaves were analyzed for micro-and macronutrients and the fruit yield was determined. Liming improved the evaluated soil chemical attributes: pH, calcium (Ca), magnesium (Mg), BS, V, and hydrogen and aluminum (H + Al) down to a depth of 60 cm of samples taken from both in and between tree rows. The Ca and Mg levels increased in the leaves also. The highest fruit yields were observed when soil base saturation reached 50 % in the rows and 65 % between rows.
Effects of liming on soil fertility, plant nutrition and guava yield
Keywords: Psidium guajava L.; Soil acidity; lime; Mineral nutrition; Psidium guajava; Solos - Acidez; Calcário; Nutrição mineral